Food and beverage industry competitiveness and halal logistics: Perspective from small and medium enterprises in Malaysia - Maizaitulaidawati Md Husin; Suzilawati Kamarudin; Adriana Mohd Rizal (Faculty of Business & Economics, Universitas Islam Indonesia, 2021)
Purpose: This paper investigates the competitiveness of the food and beverages (F&B) industry in Malaysia and examines the Small and Medium Enterprises' (SMEs) demand and key perceptions towards challenges in halal logistics. Methodology: This paper adopted SWOT analysis to understand the internal (strengths, weaknesses) and external (opportunities and threats) competitiveness of the industry. Interview sessions were conducted with 10 SMEs’ owners in the food industry from December 2020 until February 2021. Findings: The SWOT analysis identified several strengths (e.g. workforce diversity, well-established equipment, and facilities), weaknesses (e.g. a limited number of skilled workforce, lack of industrial collaboration, lack of distribution channel), opportunities (e.g. increasing food demand, advanced technology, supportive government initiatives, favorable business environment) and threats (e.g. high cost, new and changing regulation). The SMEs’ perception towards key challenges in halal logistics was also identified.Research limitations/implications: This paper provides an understanding of the competitiveness of the F&B industry, sheds light on the key challenges faced by SME owners in halal logistics, and offers strategies to solve the issues. This study, however, is limited to Malaysia’s experience. Practical implications: This paper will contribute to future studies in the similar field and offers a guide for Halal logistics players, including practitioners and policymakers, to understand their business environment better. The identification of SMEs’ SWOT will be helpful for the businesses to move forward.Originality: The value of this paper lies in the knowledge of SMEs, especially in the F&B industry.